In vitro antimicrobial activity of eight new beta-lactam antibiotics against penicillin-resistant Neisseria gonorrhoeae. - Kerbs, S B (1983)
Increasing numbers of cases of penicillin-resistant gonorrhea necessitate the evaluation of new antibiotics for treatment of this disease. We tested the susceptibility of 92 penicillinase-producing (PP) Neisseria gonorrhoeae isolates and 88 penicillin-susceptible (PS) isolates to eight new beta-lactam antibiotics. The minimal inhibitory concentrations of these antibiotics were determined by the agar plate method. PP and PS N. gonorrhoeae isolates were susceptible to clinically achievable levels of all antibiotics tested. There were, however, marked differences among the drugs with regard to the concentration required to inhibit growth. The PP N. gonorrhoeae isolates were extremely susceptible to ceftriaxone, ceftizoxime, and cefotaxime, highly susceptible to moxalactam and cefoperazone, and less susceptible to cefoxitin, ceforanide, and cefonicid (geometric mean minimal inhibitory concentrations were 0.002, 0.003, 0.007, 0.03, 0.07, 0.6, 2.4, and 3.1 micrograms/ml, respectively). Although this in vitro study showed PP N. gonorrhoeae isolates to be comparatively more susceptible to ceftriaxone, ceftizoxime, and cefotaxime than to the other antibiotics, these results may not correlate with clinical efficacy.